Evaluation of literary texts included in the Arabic language book For the third intermediate grade in light of critical thinking skills (Journal of the College of Basic Education, 2024)
The current research aims to find out: (Evaluating the literary texts included in the Arabic language book for the third intermediate grade in light of critical thinking skills): To achieve the goal of the research, the researcher adopted the descriptive approach as an approach to his study, because it is the appropriate approach to achieve the goal of the research. The research community consisted of male and female Arabic language teachers for the third intermediate grade in the six general directorates of education in the six Baghdad governorates, for the academic year 2021-2022, and their number is(1126) male and female teachers. The researcher randomly chose the research sample to be representative of the research community, as it amounted to (166) male and female teachers in the General Directorates of Education in Baghdad. The research tool was a questionnaire for critical thinking skills, and the validity of the tool (the questionnaire) was confirmed by By presenting it to the arbitrators, the questionnaire included (12) indicators, distributed over (7) skills. After collecting data and analyzing the results statistically using the weighted mean and percentage weight, the researcher reached results including: 1- Indicator (11) ranked first (following the discovery and interpretation of scientific facts) with a weighted mean (3.46) and a percentage weight (69.2%(.2- Indicator (20) (students’ ability to evaluate ideas contained in literary texts and accept and reject them) ranked sixteenth with a weighted mean (80.2) and a percentage weight (56(.In light of the results, the researcher reached conclusions including:1- The skills and indicators achieved in the book represent (92%) of critical thinking skills.2- The skills and indicators not met in the book represent a percentage of (8) critical thinking skills.The researcher made the following recommendations, including:The General Directorate of Curricula must take into account the findings of this research and work to achieve the remaining 8% skills in the Arabic language book for the third intermediate grade.The necessity of directing the colleges of education and basic education in Iraqi universities to increase interest in Arabic language teachers by including programs to prepare them for critical thinking skills before service, providing them with a set of critical thinking skills, and training them to develop them among their students through their use of modern strategies and methods that contribute to the development of critical thinking.The researcher proposed proposals including:Conduct research similar to the current research on other materials.Conduct research to reveal the availability of critical thinking skills in other stages and balance them.